Size reduction of Aspergillus versicolor fungal bioaerosols during a thermal heating process in continuous-flow system - Jung, Jae Hee; Lee, Jung Eun; Kim, Sang Soo; Bae, Gwi Nam (ELSEVIER SCI LTD, 2010)
Airborne fungi, termed fungal bioaerosols, have received attention due to their association with public health problems. The search for ways to prevent the harmful effects of fungal bioaerosols has created a high demand for research and development of efficient methods for controlling bioaerosols. We investigated variations in aerosol characteristics including total number concentration, size distribution, and surface morphology of fungal bioaerosols under a thermal heating process, a promising bioaerosol control method, in a continuous-flow system. Quantitative thermal characteristics of fungal bioaerosols were also obtained from thermogravimetric analysis. Our experimental results show that the aerodynamic and physical diameter of tested fungal bioaerosols decreased when exposed to increasing surrounding temperatures, even within a short exposure time of about 0.15 s. The instantaneous exposure to high temperature significantly changed the surface morphology of the fungal bioaerosols and caused thermal decomposition of the polymer component of the fungal cell wall. These variations in physical characteristics are closely related to the aerodynamic diameter of fungal bioaerosols. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: SHORT-TIME PASTEURIZATION; SMALL CERAMIC HEATER; HIGH-TEMPERATURE; RESPIRATORY DEPOSITION; AIR IONS; INACTIVATION; SPORES; PARTICLES; REMOVAL; INDOOR